Electrochemical creatinine determination with metal-organic framework catalyst based on copper and acetylenedicarboxylic acid - Andrei V. Okhokhonin; Alsu A. Ibatullina; Yulia V. Izmozherova; Marina I. Stepanova; Anatoliy I. Matern; Alisa N. Kozitsina (Chimica Techno Acta)
Fast and accurate determination of creatinine is critical in kidney function diagnostics. This paper discusses the usage of the metal-organic framework based on copper(II) and acetylenedicarboxylic acid (CuADCA) as a catalyst of electrochemical oxidation of creatinine, glucose and urea. CuADCA was synthesized by deprotonation with triethylamine for the first time. Successful synthesis was confirmed by FTIR and EDS. The material was characterized by SEM, EIS, and CV. CuADCA forms laminated-like flakes with diameter from 1 µm to 20 µm, which is consistent with the polymer-like structure. CV and EIS analyses showed that CuADCA immobilized on GCE acts as a catalyst in electrooxidation reaction of glucose, urea, and creatinine. The sensitivity of creatinine detection, 1057±99 µA/mM, was higher than the detection sensitivity of glucose and urea by more than 100 times with the limit of detection of 2 µM, so CuADCA is a promising material for further development of enzymeless sensors for creatinine.